Signaling the Importance of Training. Issue 7 (19th August 2014) - Towler, Annette; Watson, Aaron; Surface, Eric; Tetrick, LoisE.; Stone, DiannaL.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose In this study of 815 military personnel, we examined how perceived leader behaviors are related to trainee perceptions of leader training priorities and to trainee priority for training, and whether trainee motivation to transfer of training moderated the relationship between trainee perceptions and trainee priority for training. Design/methodology/approach Participants who were experienced job incumbents responded to a survey related to foreign language usage, training, and policy. Findings When leaders showed support for training through their actions, trainees were more likely to perceive their leaders as placing a higher priority on training. Leader behaviors predicted trainee priority to train, because trainees believed their leaders set a higher priority for training. The leader behaviors that were important for trainees' priority to train were discretionary behaviors, not those leader behaviors mandated by the organization. Trainee perceptions of leader priority were more positively predictive of trainees' priority to train for trainees with less motivation to transfer of training. Originality/value Supervisor support is an important predictor of training outcomes. We expand this literature by focusing on the signals that leaders send to their subordinates regarding training priority. Leaders who exhibited discretionary behaviors in support of training appeared to create an environment in which trainees placed greater importance on training. Organizations need to be aware that mandating training activities might not be as important as encouraging leaders to place value on discretionary activities.